Non-platinum based electrocatalysts for alkaline direct ethanol fuel cell - Nguyen, Truong Son (2012)
It is well-known that conventional fossil fuel is not going to last more than a few hundred years in the face of increasing energy demand in the developed and developing countries. Moreover, the gas emission from the combustion of fossil fuels by heat engines has been polluting the living environment and causing green-house effect. Therefore, it is urgent to find new technologies for energy conversion and power generation. Recently, direct ethanol fuel cells (DEFCs) have attracted more and more attention as clean and high efficient energy conversion devices. However, the expensive cost of Pt in the fuel cell electrocatalysts limits the commercialization of DEFCs. Pd, which is cheaper than Pt, has been found to be more active for ethanol electrooxidation in alkaline media than Pt. On the other hand, the corrosion of carbon-based catalyst supports in polymer electrolyte membrane fuel cells (PEMFCs) has been known as one of the main factors limiting the lifetime of the fuel cells. As a result, the research work in this thesis is focused on the designing of effective non-platinum based electrocatalysts for alkaline DEFCs (ADEFCs) by modifying Pd with promoters to reduce the cost of fuel cells and thus, improve their commercialization. Moreover, corrosion-resistance of titania-based materials is also studied in this work to explore their capability to replace carbon black in the role of catalyst support for ADEFCs. Firstly, alloyed PdAg nanoparticles supported on carbon black were successfully synthesized by a co-reduction method. The alloyed catalysts showed their dominant ethanol oxidation reaction (EOR) activity compared with those of Pd/C and Pt/C in alkaline solutions. Among various PdAg/C catalysts with different Ag/Pd ratios, the highest EOR performance and poisoning-tolerance were observed for 10%Pd-10%Ag/C. The excellent EOR behavior of the alloyed catalysts derived from the improvement of hydroxyl adsorption onto the catalyst surface due to the d-band center up-shift. Secondly, Tb, a rare-earth element, was used to modify Pd/C. Different Tb-promoted Pd/C catalysts were prepared and tested for EOR in alkaline condition. The catalysts displayed good activity for EOR with the most prominent performance obtained for 10%Pd-2%Tb/C. Thirdly, mesoporous titania was hydrothermally synthesized and used as an alternative support for Pd towards EOR in basic solutions. The mesoporous TiO2-supported Pd catalyst showed better activity for EOR than Pd/C and Pd/commercial TiO2 due to the mesoporosity and high hydroxyl content of mesoporous TiO2. Durability tests confirmed that Pd/mesoporous TiO2 has higher stability than the catalysts supported on carbon black and commercial TiO2. Besides the mesoporous TiO2, sub-stoichiometric TinO2n-1 was prepared from commercial TiO2 by H2 reduction. Higher EOR activity and durability were observed for Pd/TinO2n-1 in comparison with Pd/C and Pd/commercial TiO2. Finally, Nb-doping was used to improve the electrical conductivity of TiO2. Nb-doped TiO2 showed an increase of electronic conductivity with the increase of Nb-doping level. Electrochemical characterization results determined that PdAg/Nb-doped TiO2 catalysts possess outstanding catalytic activity for EOR, which is attributed to the interaction between the supports and PdAg nanoparticles. The PdAg/Nb-doped TiO2 catalysts also displayed excellent durability with the best performance obtained for PdAg/Nb0.20Ti0.80O2 and PdAg/Nb0.30Ti0.70O2. PdAg/Nb0.30Ti0.70O2 was found to have better electrocatalytic activity for EOR and higher durability in alkaline condition than PdAg/TinO2n-1 and PdAg/mesoporous TiO2.